Factors Associated with Parenting Stress in Parents of Children: A Cross-Sectional Study - Yersi Ahzani; Nur Agustini; Allenidekania Allenidekania; Fajar Tri Waluyanti; Harjoedi Adji Tjahjono (PT.Mantaya Idea Batara, 2026)
Abstrak: Background: Type 1 Diabetes requires complex lifelong care, increasing parental stress. The COVID-19 pandemic exacerbated this burden through disrupted healthcare, limited social support, and financial strain, particularly in Indonesia, where evidence on influencing factors remains limited. Methods: Cross-sectional research with consecutive sampling was conducted in the Family Association of Diabetes Sufferers in Children and Adolescents Indonesia. This study involved 136 parents who met the inclusion criteria. Multivariate linear regression analysis was performed to identify the relationship between parental characteristics and situational factors on parenting stress. A standard questionnaire and a self-administered questionnaire were used in this research. Results: The analysis demonstrated significant relationships between several variables and parenting stress. Specifically, economic status (p=0.006), marital status (p=0.031), healthcare system challenges during COVID-19 pandemic (p=0.000), social support (p=0.003), and coping mechanisms for children’s illness (p=0.047) were significantly associated with the frequency of parenting stress. Additionally, there were significant relationships between economic status (p=0.000), health care system challenges during the COVID-19 pandemic (p=0.001), and social support (p=0.015) with parenting stress based on parental difficulties. Conclusions: This study identified that parents’ coping mechanisms for managing their child’s illness and the availability of social support are critical factors influencing parenting stress. Notably, higher levels of social support were associated with lower parenting stress. These findings underscore the importance of integrating social support networks and targeted nursing interventions to alleviate parental stress and improve caregiving outcomes. Keywords: Parenting stress, Type 1 diabetes, COVID-19 pandemic, Cross-sectional study.